(3QSGdI aj GNJdGa WQb GdGSJOdGd hGSJfHGW GdGMcGes - (3GdUbQj, GdeWjQaj, GdGMSGFj, GdHMQGfj, YeGO GdOjf, CMeO Hf Rjf GdOjf Hf EHQGgje Hf UbQ, J (B1241(3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B...(3CeG HYO ajbhd GdYHO GdeScjf(B...(3Efj deG QCjJ cKQI GdGNJdGa Hjf YdeGFfG aj CcKQ WQb GdGSJOdGd hcjajI GSJfHGW GdMQGe hGdMdGd(B...s
(3BNQgG (B:s
(3hdcf dG MGLI Edi Pdc aEf CgdgG jYQahfgG hGdCZjGQ ZjQ eNGWHjf HgG hGdSdGe Ydi ef GJHY GdgOis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B1(3,U(B129s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B143s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs